Estudo do aproveitamento do rejeito da mineração de esmeraldas na produção de refratários conformados isolantes - Barros, João Alfredo de Almeida (2013)
Emerald mining is an important area of the economy in Brazil, country which is in second place among the exporting nations of this gem. Due to the process of extraction, a great amount of reject is generated. Since there is no appropriate destination, the reject is abandoned around the mining industries, contributing to environment degradation. Nowadays, some of the most relevant things to an industry in general are: energy conservation, cost reduction, quality and productivity enhancement. The production of isolating, transformed refractory materials achieves the sustainability dimension when protection of the environment is incorporated to such process. This work investigates the use of emerald mining rejects in the ceramic body of refractory materials, aiming at obtaining a product whose characteristics are compatible with commercial products and, at the same time, allow the use of such rejects to solve the environmental issue caused by its disposal in nature. X-ray fluorescence analysis show that the emerald reject obtained after the flotation to extract molybdenum and mica has 70% of silica and alumina (SiO2+Al2O3) and 21% of a basic oxides and alkaline metals and earthy alkaline mixture (Na2O, K2O, CaO e MgO). Because of the significant amount of silica and alumina present in the reject, four refractory ceramic bodies were prepared. Samples with a rectangular shape and dimensions 100x50x10 mm were pressed in a steel mold at 27,5 MPa and sintered at 1200ºC for 40 min. under environment atmosphere in a resistive oven. The sintered samples were characterized in relation to the chemical composition (FRX), mineralogical composition (DRX), microstructure (MEV) and physical and mechanical properties. The results indicate that the mixture with 45% of reject, 45% of alumina and 10% of kaolin presents a refractory quality of 1420ºC, dimensional linear variation below 2.00%, apparent specific mass of 1,56 g/cm3 and porosity of 46,68%, which demonstrates the potential use of the reject as raw material for the industry of isolating transformed refractory materials